An intellectual par excellence - Abd Razak, Dzulkifli (2006)
IT not often that a young nation like Malaysia is blessed with a gentleman, an intellectual, a thinker and a scholar par excellence, all wrapped up in one. Even then, the nation could never have enough of his services. Tan Sri Dr Noordin Sopiee passed away last year at the age of 61, after battling cancer for several months. But like all national heroes, more so the intellectual ones, there are not enough of them. Noordin will be remembered for a variety of reasons. In his various capacities, as a Press person at the New Straits Times Press to the helm of the Institute of Strategic and International Studies (ISIS), Noordin left his mark. Starting out as a journalist, he rose to became group editor of the New Straits Times in the late 1970s.